The reproduction of Colletia hystrix and late-flowering in Colletia (Rhamnaceae: Colletieae) - Medan, Diego (2015)
Plant fitness strongly depends on the timing of flower production. In temperate climates most plants bloom during a relatively well-defined peak, while comparatively few species flower before or after the community peak. Since a phylogenetical signal has been shown to exist in the determination of reproductive phenology, it is of interest to identify characters associated with the emergence of either type of behaviour. Here we report on the reproduction of the late-flowering shrub Colletia hystrix and discuss the results in the context of the whole genus Colletia. Colletia hystrix shares with its congeners deep flowers, associated with assemblages of long-mouthpart pollinators, and characters that maximise the chances of successful pollen receipt and export in a single pollinator visit (homogamy, a large stigma, and an extragynoecial compitum). Leaflessness and extreme spinescence of Colletia are suggested to be related (via compromised resource acquisition) to phenological displacement and its flower-level correlates.